Worlds of Rankings - Ringel, Leopold; Espeland, Wendy; Sauder, Michael; Werron, Tobias (Research in the sociology of organizations ;, 2021)
This volume contains an Open Access chapter. We have witnessed an avalanche of quantitative public measures over the past decades. Research in the social sciences has shown that rankings in particular are now a driving force of social change - both, desired and undesired - in many areas of modern life. This volume explores the distinct allure of rankings in diverse empirical settings such as healthcare, the IT sector, the arts, professional sports, anti-slavery advocacy, the pharma industry, and educational governance. Drawing from a rich variety of social theories and methodologies, the contributions to this volume advance our understanding of the production, institutionalization, and effects of rankings significantly, sparking new debates and suggesting promising pathways forward.